Menyulam Persahabatan Cultural Exchange Mahasiswa UNNES di Kampung Gumut, Kerling, Selangor sebagai Sarana Penguatan Identitas dan Kolaborasi Budaya - Haydnn Caesha Maulana; Shafa Maria Hanurani Putri; Widya Oktavia; Ludfi Ayu Bela Insani; Satria Ariayudha Widiatmoko (Karya Nyata : Jurnal Pengabdian kepada Masyarakat, 2025)
The Cultural Exchange program organized by students of Semarang State University (UNNES) in Kampung Gumut, Kerling, Selangor, Malaysia, is a strategic initiative in strengthening cultural identity while building a network of friendships across nations. Through a non-formal cultural diplomacy approach, this activity introduced the richness of traditional Indonesian culinary such as Soto Semarang, Kopi Tubruk Sumowono, Jamu Turmeric Asam, and Bakwan Sayur, as well as displaying traditional clothing from various regions, including Dayak, Kebaya Encim, Beskap Jawa, Kebaya Jawa, and Bali. The cross-cultural interaction created encourages open dialogue, broadens horizons, and fosters tolerance between communities. The enthusiasm of local residents, active participation in discussions, and the presence of community leaders show that cultural exchanges can be an effective medium in building social solidarity and strengthening Indonesia-Malaysia bilateral relations. This program not only provides a transformative experience for students as cultural ambassadors, but also creates a warm and meaningful communication space. With a participatory approach, this activity has the potential to open up wider collaboration opportunities in the fields of education, social, and culture. Overall, the UNNES Cultural Exchange in Malaysia is a real example of how the young generation can play an active role in cultural diplomacy, strengthen national identity, and build inclusive and sustainable international relations.